Effectiveness of ICT in attaining the Learning Outcomes on speaking skills - Bharathiraja, R. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Experts say that kids should begin to learn a foreign language from a young age; the younger the better. ―A child is born with the ability to learn any language in the world,‖ explains Caryn Antonini, creator of Early Lingo. Here, in bilingual scenario, pupils find difficult in speaking English as it is a language of foreign land, which in due course emerged as the inevitable language of this land for acquiring knowledge and employment. Learning Outcomes prescribed by NCERT for class VII includes various L. Os on speaking skills. There is fear factor among the children obstructing them from speaking in English. A study is carried out to find the impact of using ICT for developing speaking skills of students studying through their native language (Tamil Medium) along with students learning through English Medium. The performances of the students are evaluated by considering the following parameters viz. Vocabulary, sentence formation, relevance and fluency. The evaluation was conducted at the start and end of the project. Each parameter has 5 rating scale. Poor, fair, Good, Very good and Excellent.   It is observed that the there is least difference in speaking skill of Tamil Medium students with that of English Medium Students. Though there is vast gap in exposure of English is concern, English medium students had normally an upper edge over Tamil medium students in exposure to English. But using ICT in enhancing the speaking skills, filled the gap, aroused the curiosity to speak in English and showed ample improvement in speaking skill of Tamil Medium Students. ICT helps in attaining Learning Outcomes on speaking skills